Театрально-видовищні простори в історичних українських культурно-просвітницьких будівлях Галичини - Копиляк, І. М.; Kopulyak, I. M. (Видавництво Львівської політехніки, 2019)
Розглянуто ключові етапи зародження та розвитку українського театру в Галичині та його зв’язок із діяльністю мережі українських культурно-просвітницьких будівель.

The foundation to genesis of Ukrainian theatre in Galicia could be put by an ancient ceremonial theatre, as a peculiar educational performance, that is brining the experience from the depth of the ages. During a long period of time folk ceremonial performances were taking place mostly in the open air. City streets, squares, yards were the ground for them. Italian yard in Korniakt kamienica (stone tenement) in Lviv, where the first professional plays were shown, has become the first permanent palace building with performing direction. The plays of professional touring troupes as well as local theatrical groups were also taking place in Jesuit college at the end of the 18th – first half of the 19th centuries. With the start of Greek Catholic Theological seminary functioning in 1783 the tradition of arranging theatrical performances is appearing. Theological Seminary theatre has set up the basis for further development of Ukrainian theatrical movement. In 1852, on Old university ruins a Community house was built and it is the first main tenement for Ukrainian professional theatre as on March 29, 1864 the premiere of “Marusia” play staged by the first professional Ukrainian Galician theatre “Ruska Besida” took place here. The stage of the building of insurance community “Dnister” has not been less important for Ukrainian theatre; the stage was built in Ruska street in 1905 by the project of I. Levynskyi, T. Obminskyi and O. Lushpynskyi. In 1908 it was here that a famous director and actor Les Kurbas made his debut. He staged the play “Jews” by Ye. Chyrkov and played the main role in it. The development of theatrical art can be observed at the beginning of the 20th century in Lviv, a big amount of drama groups appears. Archives confirm that leisure of Ukrainians at that time in Lviv was closely connected with such societies as “Fronzin”, “Gviazda”, “Yad Kharuzim”, restaurants “Bristol” and “George”. After the defeat of Ukrainian forces in Polish-Ukrainian war in 1918, the reconstructed hall and stage of M. Lysenko Music Institute became the only ground for activity of Ukrainian theatre during the 20–30s. During the second half of the 19th – beginning of the 20th centuries the city of Kolomyia was among the leading, second in its importance after Lviv, cultural centres of Galicia. Back in 1848 Ivan Ozarkevych founded the first Ukrainian folk amateur theatre here. On June 8, 1848 the premiere of the first play “Girl to be married, or endearment cannot be forced” (“Дівка на виданню, або На милування нема силування”) based on the play of Ivan Kotliarevskyi took place. On October 19 the theatre staged the play “Girl to be married” (“Дівка на виданню”) in front of the delegates of the Gathering of Rus researchers which took place in Lviv on the premises of Greek Catholic seminary. According to I. Franko, this event has triggered Ukrainian theatrical movement in Lviv and Galicia. Starting from 1901 residents of Kolomyia listened to theatrical performances and concerts of famous Ukrainian artists, singers, musicians, in particular of Solomiia Krushelnytska, Mykola Lysenko, in the hall of a Community house. Since 1920 the concerts, meetings and Ukrainian activities were taking place in the house of craftsmen society “Gviazda”. Similar examples can be found at other cities and villages of that time Galicia, such as Przemysl, Stryi, Kamianka-Buska, Sudova Vyshnia, Yavoriv and many others. Consequently, it can be stated that the development and activity of Ukrainian theatre are really closely, and sometimes inseparably connected with the activity of a network of Ukrainian cultural and educational institutions.
Architecture of theaters of national communities in Ukraine as centres of intercultural dialogue
Keywords: клубна будівля; український театр; Народний дім; club buildings; Ukrainian theater; People’s House; 727.9